The two possibilities for y are y = -12 and y = 7.
In order to solve this, we first just factor the equation. In order to factor a quadratic like this, we look for factors of the last number (-84) that add up to the middle number (5). In order to find that, we just need to list the factors.
1 * -84
-1 * 84
2 * -42
-2 * 42
3 * -28
-3 * 28
4 * -21
-4 * 21
7 * -12
- 7 * 12
This last factor is the one that adds to 5. Now we stick these two numbers along with y's into parenthesis.
(y - 7)(y + 12)
Now to solve, we can set each parenthesis equal to 0 to solve.
y - 7 = 0
y = 7
y + 12 = 0
y = -12